A prospective study of physical activity and fecundability in women with a history of pregnancy loss. Issue 7 (10th April 2018) - Russo, Lindsey M; Whitcomb, Brian W; Mumford, Sunni L; Hawkins, Marquis; Radin, Rose G; Schliep, Karen C; Silver, Robert M; Perkins, Neil J; Kim, Keewan; Omosigho, Ukpebo R; Kuhr, Daniel L; Holland, Tiffany L; et al.
Abstract: STUDY QUESTION: Is physical activity (PA) associated with fecundability in women with a history of prior pregnancy loss? SUMMARY ANSWER: Higher fecundability was related to walking among overweight/obese women and to vigorous PA in women overall. WHAT IS KNOWN ALREADY: PA may influence fecundability through altered endocrine function. Studies evaluating this association have primarily utilized Internet-based recruitment and self-report for pregnancy assessment and have yielded conflicting results. STUDY DESIGN, SIZE, DURATION: This is a secondary analysis of the Effects of Aspirin in Gestation and Reproduction (EAGeR) trial (2007–2011), a multisite, randomized controlled trial of preconception-initiated low-dose aspirin. PARTICIPANTS/MATERIALS, SETTING, METHODS: Healthy women ( n = 1214), aged 18–40 and with 1–2 prior pregnancy losses, were recruited from four US medical centers. Participants were followed for up to six menstrual cycles while attempting pregnancy and through pregnancy for those who became pregnant. Time to hCG detected pregnancy was assessed using discrete-time Cox proportional hazard models to estimate fecundability odds ratios (FOR) adjusted for covariates, accounting for left truncation and right censoring. MAIN RESULTS AND THE ROLE OF CHANCE: The association of walking with fecundability varied significantly by BMI ( P -interaction = 0.01). Among overweight/obese women, walking ≥10 min at a time was related to improved fecundability (FOR = 1.82, 95% CI: 1.19, 2.77). In adjusted models, women reporting >4 h/wk of vigorous activity had significantly higher fecundability (FOR = 1.69, 95% CI: 1.24, 2.31) compared to no vigorous activity. Associations of vigorous activity with fecundability were not significantly different by BMI ( P -interaction = 0.9). Moderate activity, sitting, and International Physical Activity Questionnaire (IPAQ) categories were not associated with fecundability overall or in BMI-stratified analyses. LIMITATIONS, REASONS FOR CAUTION: Some misclassification of PA levels as determined by the short form of the IPAQ is likely to have occurred, and may have led to non-differential misclassification of exposure in our study. Information on diet and change in BMI was not collected and may have contributed to some residual confounding in our results. The generalizability of our results may be limited as our population consisted of women with a history of one or two pregnancy losses. WIDER IMPLICATIONS OF THE FINDINGS: These findings provide positive evidence for the benefits of PA in women attempting pregnancy, especially for walking among those with higher BMI. Further study is necessary to clarify possible mechanisms through which walking and vigorous activity might affect time-to-pregnancy. STUDY FUNDING/COMPETING INTEREST(S): This work was funded by the Intramural Research Program of the Eunice Kennedy Shriver National Institute of Child Health and Human Development. The authors report no conflicts of interest in this work. TRIAL REGISTRATION NUMBER: #NCT00467363.